2009
DOI: 10.1186/cc7784
|View full text |Cite
|
Sign up to set email alerts
|

Delivered dose of renal replacement therapy and mortality in critically ill patients with acute kidney injury

Abstract: Introduction The optimal dialysis dose for the treatment of acute kidney injury (AKI) is controversial. We sought to evaluate the relationship between renal replacement therapy (RRT) dose and outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
144
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(159 citation statements)
references
References 36 publications
(52 reference statements)
7
144
2
3
Order By: Relevance
“…Our study demonstrated a shorter duration of ICU stay and a trend for a shorter duration of RRT with the lower-volume protocol, in contrast to previous reports, where high-volume therapy was associated with a shorter duration of RRT, ICU stay and/or ventilatory support [1,4]. In our study, this difference is most likely to reflect differences between the two cohorts rather than an effect of the RRT protocol switch; the low-volume cohort had a higher incidence of CKD at baseline, and fewer patients required ventilatory support.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Our study demonstrated a shorter duration of ICU stay and a trend for a shorter duration of RRT with the lower-volume protocol, in contrast to previous reports, where high-volume therapy was associated with a shorter duration of RRT, ICU stay and/or ventilatory support [1,4]. In our study, this difference is most likely to reflect differences between the two cohorts rather than an effect of the RRT protocol switch; the low-volume cohort had a higher incidence of CKD at baseline, and fewer patients required ventilatory support.…”
Section: Discussioncontrasting
confidence: 55%
“…Small cohort numbers, the heterogeneous nature of patients included, and a lack of standardisation of the RRT protocols, particularly when multiple centres and/or countries were included, meant that the conclusions of the studies were far from definitive. Actual practice on ICUs was seen to be highly variable, with some centres adopting predominately high-volume and others low-volume protocols [4,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…82 However, others have failed to reproduce these results. 33,67,83,84 It is now felt that there is a threshold of dose for both intermittent and continuous therapies in critically ill patients above which no further benefit is seen, 85 which appears to be between 20 and 35 ml/kg/hour based on previous studies. 67,82,84 The effects of RRT on the critically ill patient has been studied using a variety of biomarkers from urea to b2 microglobulin to cytokines, yet Kt/V for urea is the most consistently studied in large populations.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…33,67,83,84 It is now felt that there is a threshold of dose for both intermittent and continuous therapies in critically ill patients above which no further benefit is seen, 85 which appears to be between 20 and 35 ml/kg/hour based on previous studies. 67,82,84 The effects of RRT on the critically ill patient has been studied using a variety of biomarkers from urea to b2 microglobulin to cytokines, yet Kt/V for urea is the most consistently studied in large populations. However, it is unknown whether this is an adequate surrogate marker for the overall effects of blood purification that occurs during RRT in the critically ill. 85 The instantaneous clearance (K) for intermittent therapy is much higher than continuous therapy due to operational characteristics (Qb, Qd and Qf rates), yet the efficacy of continuous therapies is greater due to the duration.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Most nephrologists may be more familiarand therefore more comfortable-with modern HD machines and their precise volumetric systems that guide fluid removal. With regard to clearances, multiple studies have evaluated the dose of HD or continuous RRT for AKI (15)(16)(17), but virtually no data on the optimal dose of PD in that setting are available (2). It is therefore not surprising that nearly 70% of respondents were uncertain about an appropriate PD dose.…”
Section: Discussionmentioning
confidence: 99%